The Opportunity Analyses of Using Thermosyphons in Cooling Systems of Power Transformers on Thermal Stations; MATEC Web of Conferences; Vol. 72 : Heat and Mass Transfer in the System of Thermal Modes of Energy – Technical and Technological Equipment (HMTTSC-2016) - Nurpeiis А. Е. Atlant Ediluly (2016, 2016)
Title screen